(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
It was investigated effects of training psychology students in the application of a software. The teaching conditions had been: 1 presentation of exercises in the classroom; 2. visit to the laboratory, which included presentation of how the computerized program works; 3. simulation of settings in which the program was applied; 4. participative supervision of the participant’s performance; 5. reading of the manual with written instructions, and a follow up on the upholding of learning in the participant’s. The results are of nine participants, having been manipulated the order of presentation of the written instructions: group A, in the beginning (n=5); group B, in the end (n=2); and group C that did not have this condition (n=2). The behavior-target had been listed and it was observed if they “they were carried through”, “not carried through” or “carried through with aid” for the participants. It had increase in the averages in the “accomplishment” of the behavior-target and reduction in the “not accomplishment” and “accomplishment with aid”, for the three groups. With these results, it is possible to affirm that it had impact of the conditions of education in the improvement of the performance for the participants.